Information Security Management Requirments Model Through Data Life Cycle (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Abstract- information security management model throughthe data life cycle is a model that can help us to follow andunderstand the strategy life of the institution anddetermining all probabilities of threats and vulnerabilities ofoccurrence and outcomes through implementing it withinthe institution. The data life cycle has been chosen that thedata life cycle management enables us to understand ourdata, which is an extremely valuable business asset andwhich must be managed properly, to ensure business successand regulatory compliance. Understanding data life cyclemanagement means to classify and determine rules,responsibilities and IT needed and determine therequirement to business targets done in the best way, herewe can say that it is the way to find out the weakness in thedata process and helping us to determine security technicalrequirement and provide the security policy.